Editor's Choice – Ten-year Experience with Endovascular Repair of Thoracoabdominal Aortic Aneurysms: Results from 166 Consecutive Patients. Issue 5 (May 2015) - Verhoeven, E.L.G.; Katsargyris, A.; Bekkema, F.; Oikonomou, K.; Zeebregts, C.J.A.M.; Ritter, W.; Tielliu, I.F.J.
Abstract : Objective: To present a 10 year experience with endovascular thoracoabdominal aortic aneurysm (TAAA) repair using fenestrated and branched stent grafts. Materials and methods: Consecutive patients with TAAA treated with fenestrated and branched stent grafts within the period January 2004–December 2013. Data were collected prospectively. Results: 166 patients (125 male, 41 female, mean age 68.8 ± 7.6 years) were treated. The mean TAAA diameter was 71 ± 9.3 mm. Types of TAAA were: type I, n  = 12 (7.2%), type II, n  = 50 (30.1%), type III, n  = 53 (31.9%), type IV, n  = 41 (24.8%), and type V, n  = 10 (6%). Fifteen (9%) patients had an acute TAAA (11 contained rupture, 4 symptomatic). One hundred and eight (65%) patients were refused for open surgery earlier. Seventy eight (47%) patients had previously undergone one or more open/endovascular aortic procedures. Technical success was 95% (157/166). Thirty day operative mortality was 7.8% (13/166), with an in hospital mortality of 9% (15/166). Peri-operative spinal cord ischemia (SCI) was observed in 15 patients (9%), including permanent paraplegia in two (1.2%). Mean follow up was 29.2 ± 21 months. During follow up 40 patients died, two of them probably from aneurysm related cause. Re-intervention, mostly by endovascular means, was needed in 40 (24%) patients. Estimated survival at 1, 2, and 5 years was 83% ± 3%, 78% ± 3.5%, and 66.6% ± 6.1%, respectively. Estimated target vessel stent patency at 1, 2, and 5 years was 98% ± 0.6%, 97% ± 0.8%, and 94.2% ± 1.5%, respectively. Estimated freedom from re-intervention at 1 and 3 years was 88.3% ± 2.7%, and 78.4% ± 4.5%, respectively. Conclusions: Endovascular repair of TAAA with fenestrated and branched stent grafts in high volume centers appears safe and effective in the mid-term in a high risk patient cohort. A considerable reintervention rate should be acknowledged, however.